Extreme Resistance to Viruses in Potato and Soybean - Ross, Brian T.; Zidack, Nina K.; Flenniken, Michelle L. (Frontiers in Plant Science, 2021)
Plant pathogens, including viruses, negatively impact global crop production. Plants have evolved complex immune responses to pathogens. These responses are often controlled by nucleotide-binding leucine-rich repeat proteins (NLRs), which recognize intracellular, pathogen-derived proteins. Genetic resistance to plant viruses is often phenotypically characterized by programmed cell death at or near the infection site, a reaction termed the hypersensitive response. Although visualization of the hypersensitive response is often used as a hallmark of resistance, the molecular mechanisms leading to the hypersensitive response and associated cell death vary. Plants with extreme resistance to viruses rarely exhibit symptoms and have little to no detectable virus replication or spread beyond the infection site. Both extreme resistance and the hypersensitive response can be activated by the same NLR genes. In many cases, genes that normally provide an extreme resistance phenotype can be stimulated to cause a hypersensitive response by experimentally increasing cellular levels of pathogen-derived elicitor protein(s). The molecular mechanisms of extreme resistance and its relationship to the hypersensitive response are largely uncharacterized. Studies on potato and soybean cultivars that are resistant to strains of Potato virus Y, Potato virus X, and Soybean mosaic virus indicate that abscisic acid-mediated signaling and NLR nuclear translocation are important for the extreme resistance response. Recent research also indicates that some of the same proteins are involved in both extreme resistance and the hypersensitive response. Herein, we review and synthesize published studies on extreme resistance in potato and soybean, and describe studies in additional species, including model plant species, to highlight future research avenues that may bridge the gaps in our knowledge of plant antiviral defense mechanisms.